Gain Insight into Sound Change Tendency among Thai Students - Agustine Andriana Ayu Mahardika; Ouda Teda Ena (English Language in Focus (ELIF), 2022)
Good pronunciation leads to the clarity of understanding and delivering a word in daily communication and context. Since pronunciation is considered one of the problems for Thai students, this research investigated some sound changes of English words made by Thai students. ten sophomore students of English for Liberal Art in Xavier Learning Community Thailand were the participants in this research. one research question to be answered in this research is “what are common factors affecting Thai students’ English sound change?” Mixed-method was implemented to answer the research question and discover Thai students’ English mispronunciation. The focus of this study is to seek the common factors influencing Thai students’ English mispronunciation. The instruments to gather the data in this research are questionnaires and interviews. The result showed that five major problems are affecting Thai students’ English mispronunciation namely mother tongue, motivation, age, and intonation. Language change also becomes one of the factors affecting sound change among Thai students. This research concluded that to master the English language, L2 students should be more attentive to learning English. L2 students must also realize the importance of learning English pronunciation. This research has implications for the students, thesis advisors, and future researchers.